2018
DOI: 10.1021/acschembio.8b00144
|View full text |Cite
|
Sign up to set email alerts
|

Different Benzodiazepines Bind with Distinct Binding Modes to GABAA Receptors

Abstract: Benzodiazepines are clinically relevant drugs that bind to GABAA neurotransmitter receptors at the α+/γ2– interfaces and thereby enhance GABA-induced chloride ion flux leading to neuronal hyperpolarization. However, the structural basis of benzodiazepine interactions with their high-affinity site at GABAA receptors is controversially debated in the literature, and in silico studies led to discrepant binding mode hypotheses. In this study, computational docking of diazepam into α+/γ2– homology models suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The (S)-methylated compound SH-I-055 was ~3 times less potent than XliHeII-048, and the (R)-methylated compound SH-I-060 was essentially inactive. This schistosome SAR is distinct from the binding of imidazobenzodiazepines to mammalian GABA A Rs, where (S) and (R) isomers have roughly equivalent binding affinities [52]. The halogen on the phenyl C2’ position of MCLZ seems important for schistosome activity, given that nitrazepam (inactive against parasites) differs from clonazepam (movement IC 50 1.9 μM) in that the phenyl ring is unsubstituted.…”
Section: Discussionmentioning
confidence: 99%
“…The (S)-methylated compound SH-I-055 was ~3 times less potent than XliHeII-048, and the (R)-methylated compound SH-I-060 was essentially inactive. This schistosome SAR is distinct from the binding of imidazobenzodiazepines to mammalian GABA A Rs, where (S) and (R) isomers have roughly equivalent binding affinities [52]. The halogen on the phenyl C2’ position of MCLZ seems important for schistosome activity, given that nitrazepam (inactive against parasites) differs from clonazepam (movement IC 50 1.9 μM) in that the phenyl ring is unsubstituted.…”
Section: Discussionmentioning
confidence: 99%
“…R-substituted chiral analogues of SH53d-ester have been proposed previously to utilize BMI (Elgarf et al, 2018), which later was observed experimentally for flumazenil in the 6D6T and 6D6U structures (Zhu et al, 2018). For the triazolobenzodiazepine alprazolam on the other hand, a binding mode was observed experimentally which corresponds to BMII (Richter et al, 2012;Middendorp et al, 2014;Masiulis et al, 2019).…”
Section: Resultsmentioning
confidence: 90%
“…In order to provide a structural hypothesis for the extraordinary potency preference of the novel ligand SH53d-acid, we performed a computational study utilizing the recently published flumazenil-and alprazolam-bound structures PDB IDs 6D6T and 6D6U (Zhu et al, 2018) and PDB ID 6HUO (Masiulis et al, 2019), together with homology models and computational docking as established in our labs (Elgarf et al, 2018;Siebert et al, 2018). Computational docking has resulted in two different binding modes as candidates for benzodiazepine and imidazobenzodiazepine based ligands, previously termed BMI and BMII (Richter et al, 2012;Middendorp et al, 2014;Elgarf et al, 2018;Siebert et al, 2018). The This article has not been copyedited and formatted.…”
Section: Resultsmentioning
confidence: 99%
“…Mice and humans, for example, are typically considered to be highly social creatures 8 . When their social needs are not filled, they can experience debilitating outcomes 1,9 . Some species (and individuals within a species), however, are more solitary, or even avoid social interactions 10 .…”
Section: Years Agomentioning
confidence: 99%
“…It should be noted, however, that the receptor conformations stabilized by flumazenil must be different from that stabilized by diazepam, so the idea that diazepam would dock into the reported structure in a similar way to flumazenil is questionable. A recent study 9 has shown that benzodiazepines whose structures are similar to that of flumazenil use BM I, whereas those similar to diazepam use BM II. Thus, the positioning of diazepam postulated by Zhu et al will probably need to be revised.…”
mentioning
confidence: 99%